Application of Alternating Current (AC) Generators in Turbine Systems for Sustainable Lighting Solutions in Rice Fields Near Beron Reservoir - Avada Rifqi Insani (Maritime in Community Service and Empowerment, 2023)
Beron Reservoir, located near rice fields, channels water into the surrounding agricultural lands. The water flow from this reservoir has the potential to be utilized for providing lighting to rice fields at night, optimizing the photosynthesis process for rice plants. The river flow rate, measured at approximately 1.9 m/s, is considered relatively low, making it challenging to generate large-scale electrical energy. This scientific study explores the application of generators in turbine systems to harness the water flow from the reservoir. Data was collected through direct observation and secondary references, acknowledging the potential risks of failure during the development process. The experimental results showed a 2:1 loss ratio in the generator’s operation. The average output voltage produced was 2.19V. Testing conducted at five different times over a single day confirmed that the generator system could be applied for the intended purpose.